The potential of the natural gas grid to accommodate hydrogen as an energy vector in transition towards a fully renewable energy system. (1st May 2022) - Danieli, Piero; Lazzaretto, Andrea; Al-Zaili, Jafar; Sayma, Abdulnaser; Masi, Massimo; Carraro, Gianluca
Highlights: Gas grid working with hydrogen/methane can make dispatchable renewable electricity. No retrofitting of the grid is required until 50% of RES share. Till 50% of RES share, it is convenient to use hydrogen only to shave the RES peaks. Hydrogen injected in the grid allows converting renewable electricity into heat. Gas grid can be used as unique energy storage system till 65% of RES share. Abstract: The temporal and geographical availability of renewable energy sources is highly variable, which imposes the importance of correct choices for energy storage and energy transport systems. This paper presents a smart strategy to utilize the natural gas distribution grid to transport and store the hydrogen. The goal is twofold: evaluating the capacity limits of the grid to accommodate "green hydrogen" for preset increasing shares of renewable energy sources (RESs) and determining at the same time the optimal mix of wind, photovoltaic (PV), biomethane and power-to-gas systems that minimizes the investment and operation costs. To this end, the energy supply system of an entire country is modelled and optimized considering the real characteristics and pressure levels of the gas grid, which is assumed to be the only storage mechanism of green hydrogen. The operational concept is to fill up the gas grid with hydrogen during the day and with natural gas during the night while always consuming the natural gas-hydrogen blend. Green hydrogen is generated by electrolysers powered by PVs, wind turbines and biomethane power systems. Results of the optimizations showed that: i) as long as the share of RES does not exceed 20%, there is no need to use the gas grid as RES storage system, ii) from 20 to 50% of RES share the gas grid receives the surplus of electricity in the peaks that would be necessary to "complete" the dispatchability of RES electricity, iii) above 50%, the excess of electricity in the peaks has to be used to generate the thermal energy required by the consumers. The gas grid can be used as unique renewable energy carrier and storage system up to 65% of RES share.